Exoskeletal and eye repair in Dalmanitina socialis (Trilobita): An example of blastemal regeneration in the Ordovician - Fatka, Oldřich; Budil, Petr; Zicha, Ondřej (International journal of paleopathology, 2021)
OBJECTIVE: To analyze anomalies of a biomineralized exoskeleton of a trilobite. MATERIALS: A specimen of Dalmanitina socialis from the Upper Ordovician Letná Formation at Veselá near Beroun, Czechoslovakia, curated at the Czech Geological Survey in Prague. METHODS: The internal mold and external mold and latex casts were coated with ammonium chloride sublimate and photographed. RESULTS: A substantial reduction of the eye surface associated with changes in morphology and surface structure was noted. CONCLUSIONS: The anomaly is believed to be the result of a healed injury after an unsuccessful predatory attack. Based on the presumed mechanism of injury, a 'large arthropod' is proposed to be the potential attacker. SIGNIFICANCE: The low incidence of sublethal attack to cephala in collections of Cambrian to Carboniferous trilobites implies that most such attacks were fatal, rendering this specimen unique and capable of providing insight into healing processes. LIMITATIONS: Post-mortem damage rendered analysis difficult. SUGGESTIONSFOR FURTHER RESEARCH: Exploration of other cases of healed trauma in order to understand Ordovician ecosystems.
Keywords: pitva; zkameněliny; Fossils; Regeneration; regenerace; zvířata; Autopsy; ekosystém; členovci; Animals; Arthropods; Ecosystem